Housing cooperatives and struggle for housing in Rio de Janeiro: two self-managed experiences in Jacarepaguá (PerCursos, 2023)
The present article proposes reflections based on the actions of the Popular Housing Union of Rio de Janeiro, and its trajectory of struggle for housing and for self-management in housing, specifically in the Jacarepaguá region. The presented section seeks to analyze two distinct moments of the movement's performance: a first housing cooperative built in the 1990s, without public resources, and with effective support from the local parish, and the second housing cooperative inaugurated in 2015, with funding from the extinct federal program Minha Casa Minha Vida (MCMV), in its strand called MCMV Entidades. An ethnography was carried out with the movement and the subjects involved between 2014 and 2019, for a doctoral thesis, and later, the research continued from a post-doctorate conducted in 2020 and 2021. Interviews were conducted based on a semi-structured script. The objective of the article is to analyze the performance of the movement and the subjects involved in the context of the struggle for housing in the two moments mentioned above and the unfolding of these struggles in contemporary times.
Keywords: struggle for housing; UMP-RJ; housing self-management; popular movement; housing cooperative